Communication Skills Profile of Elementary Teacher Education Students in STEM-based Natural Science Online Learning - Duhita Savira Wardani; Jajang Bayu Kelana; Zingiswa Mybert Monica Jojo (Universitas Muhammadiyah Surakarta, 2021)
This study aimed to determine the communication skill profile of Elementary Teacher Education (ETE) students enrolled in natural science online learning-based STEM. Pre-experimental research with a one-shot case study design was used in this study. The study's sample consisted of 25 ETE students from a university in Cimahi. Observation and documentation were the techniques used in this study. The paired sample t-test was used to analyze the data. The descriptive analysis and hypothesis testing with the t-test were used to check the data validity. The findings of this study revealed that (1) there is an effect of STEM-based online science learning on ETE students' communication skills, (2) that most students are still in the Intermediate category for written communication and